Prediction of Cardiovascular Events and All-Cause Mortality With Brachial-Ankle Elasticity Index: A Systematic Review and Meta-Analysis - Vlachopoulos, Charalambos; Aznaouridis, Konstantinos; Terentes-Printzios, Dimitrios; Ioakeimidis, Nikolaos; Stefanadis, Christodoulos (Hypertension (Dallas, Tex. 1979), 2012)
Brachial-ankle elasticity index (baEI; also known as brachial-ankle pulse wave velocity) has been proposed as a surrogate end point for cardiovascular disease. We performed a meta-analysis of longitudinal cohort studies for determining the ability of baEI to predict risk of cardiovascular events and all-cause mortality and dissecting factors influencing this predictive ability. Multiple online databases, reference lists from retrieved articles, and abstracts from international cardiovascular conventions were searched until April 2012. Longitudinal cohort studies that reported associations of baEI with clinical risk were included. Of the 18 studies included (8169 participants; mean follow-up, 3.6 years), 15 reported results on total cardiovascular events (5544 individuals), 7 on cardiovascular mortality (2274 individuals), and 9 on all-cause mortality (5097 individuals). The pooled relative risks for total cardiovascular events, cardiovascular mortality, and all-cause mortality were 2.95 (95% CI, 1.63–5.33), 5.36 (95% CI, 2.17–13.27), and 2.45 (95% CI, 1.56–3.86), respectively, for subjects with high versus low baEI (all P<0.001). An increase in baEI by 1 m/s corresponded with an increase of 12%, 13%, and 6% in total cardiovascular events, cardiovascular mortality, and all-cause mortality, respectively. We conclude that baEI is associated with increased risk of total cardiovascular events and all-cause mortality. Issues such as expansion of data to non-Asian populations, validation of path length estimation, determination of reference values, and prospective comparison with carotid-femoral pulse wave velocity remain to be resolved.